Coupling of the expression of proliferation and epithelialmesenchymal transition markers with the histidine-rich glycoprotein HRG mRNA expression in breast diseases - S. А. Arkhipov; А. А. Studenikina; V. V. Arkhipova; А. V. Proskura; А. I. Autenshlyus (Сибирский научный медицинский журнал)
Non-malignant breast diseases (NMBD) may increase the risk of developing a malignant neoplasm. Therefore, it seems relevant to search for criteria for cell malignancy in NMBD. Aim of the study was to investigate the relationship between expression of proliferation and epithelial-mesenchymal transition (EMT) markers and histidine-rich glycoprotein (HRG) mRNA in breast diseases. Material and methods. In breast biopsy specimens of 37 patients with invasive carcinoma of a non-specific type (ICNT) and 17 patients with NMBD expression of proliferation markers (Ki-67, cyclin D1 (CCND1)) and EMT markers (E-cadherin (CDH1), type II collagen (CII) and β1-integrin (CD29)) was determined immunohistochemically. HRG mRNA expression was estimated using real time PCR. Results. HRG mRNA expression was detected in 91.9 % cases (34 of 37) in ICNT, 82.4 % (14 of 17) in NMBD and in the latter case was inversely related to the expression of CDH1, CD29 and Ki-67. A direct relationship has been established between the presence of Ki-67 and CCND1, CII, between CCND1 and CD29 in NMBD. In patients with ICNT, a direct correlation was found between the HRG mRNA expression and the presence of CII, and an inverse correlation between the number of cells containing CII and CD29. It was found that in ICNT and NMBD with the presence of HRG mRNA expression, the CDH1 expression is less than in its absence. Conclusions. Indicators of HRG mRNA expression in NMBD, combined with the assessment of proliferation and EMT markers, can be useful in developing criteria for cell malignancy in benign breast diseases.